1988
DOI: 10.1111/j.1399-0039.1988.tb02074.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HLA antigens in the native South Indian Tamil Hindus

Abstract: Blood samples from 240 unrelated healthy Tamil-speaking South Indian Hindus residing in Madras (capital city of Tamil Nadu, India) were screened for HLA-A and -B antigen profiles. Antigen, gene and haplotype frequencies were calculated and compared with the literature. Tamil Hindus lack A31, A32, Aw33, B16, B21 and Bw41. However, except for minor differences (low occurrence of Aw19 antigen), the South Indians show similarity to North Indian and other Indian groups. The data confirm once more that the haplotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Serological data on the incidence of HLA‐B27 in various caste groups studied highlights the heterogeneity of this allele in the population from Mumbai and correlates well with other studies on the Indian population (4–15). Other molecular studies from Mumbai (17, 24) and North India (18, 19) confirm the ubiquitous distribution of HLA‐B*2702, B*2704, B*2705 and B*2707 while B*2708, B*2714 and B*2718 seem to be restricted in their distribution.…”
Section: Hla‐b27 Subtype Distribution Among Different Caste Groups Frsupporting
confidence: 84%
See 2 more Smart Citations
“…Serological data on the incidence of HLA‐B27 in various caste groups studied highlights the heterogeneity of this allele in the population from Mumbai and correlates well with other studies on the Indian population (4–15). Other molecular studies from Mumbai (17, 24) and North India (18, 19) confirm the ubiquitous distribution of HLA‐B*2702, B*2704, B*2705 and B*2707 while B*2708, B*2714 and B*2718 seem to be restricted in their distribution.…”
Section: Hla‐b27 Subtype Distribution Among Different Caste Groups Frsupporting
confidence: 84%
“…Chhaya : HLA -B27 in Western India Tissue Antigens 2005: 66: 48-50 population from Mumbai and correlates well with other studies on the Indian population(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Other molecular studies from Mumbai(17,24) and North India(18,19) confirm the ubiquitous distribution of HLA-B*2702, B*2704, B*2705 and B*2707 while B*2708, B*2714…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Two previous indigenous Hindu sam ples [Mehra et al, 1986;Selvakumar et al, 1988] suggested only limited heterogeneity between the Hindu populations of the North and South of India. Comparison of the phenotype frequencies of the present Hindu sample with these, however, did not support this suggestion.…”
Section: Resultsmentioning
confidence: 99%
“…During the last two decades, several in vestigations have established the HLA al lele frequency distributions in Indian im migrants living in Europe, Canada and Africa [Singal, 1972;Festenstein et a!., 1972;Brain and Hammond, 1972;Ham mond et al, 1975;Mittal et al, 1982], Re cently, HLA studies have been extended to several indigenous caste, tribal, and re gional groups of India [Bale et al, 1980;Wadia et al, 1980;Papiha et al, 1983;Verma et al, 1983;Pitchappan et al, 1984;Mehra et al, 1986: Rajashekar et al, 1987Selvakumar et al, 1987Selvakumar et al, , 1988. Consider ing the great diversity among the popula tions of the Indian region, these reports are just the beginning of the collection of the vital genetic information, required to understand the genetic variability and its maintenance, historical movements and the relationship among the populations.…”
mentioning
confidence: 99%